2019
DOI: 10.3171/2018.8.spine18553
|View full text |Cite
|
Sign up to set email alerts
|

How do physician demographics, training, social media usage, online presence, and wait times influence online physician review scores for spine surgeons?

Abstract: OBJECTIVEThe purpose of this study was to assess the impact of certain demographics, social media usage, and physician review website variables for spine surgeons across Healthgrades.com (Healthgrades), Vitals.com (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
57
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 11 publications
4
57
0
1
Order By: Relevance
“…These findings expand upon previous studies which demonstrate the power of SM to influence PRWs among spine and joint replacement surgeons. 13,15,16,21 These results present SM as a tool for physicians to help shape his/her online image, which may prove to be an influential factor in the acquisition of new patients. The potential influence of the online physician review was demonstrated in a study which examined the effects of a single positive review posted to a social media website, on a clinic's cosmetic surgery volume.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…These findings expand upon previous studies which demonstrate the power of SM to influence PRWs among spine and joint replacement surgeons. 13,15,16,21 These results present SM as a tool for physicians to help shape his/her online image, which may prove to be an influential factor in the acquisition of new patients. The potential influence of the online physician review was demonstrated in a study which examined the effects of a single positive review posted to a social media website, on a clinic's cosmetic surgery volume.…”
Section: Discussionmentioning
confidence: 77%
“…A previous study examined online reviews among spinal surgeons and revealed similar results, where the level of training correlated with differences in PRW ratings, with neurosurgery trained physicians receiving higher grades when compared to those who were orthopaedic trained. 13 The three PRWs investigated were positively correlated with one another. The weak to moderate Pearson correlation observed between them indicates that the ratings for a physician on one website do not necessarily correlate strongly to their rating on another rating website.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The impact of SM with online reviews has been studied in the past year within spine surgery, 6 but there have not been any published studies that analyzed the impact of SM in joint reconstruction. With about 65% of older adults now using SM, 7 a SM presence and online physician ratings are more important than ever for the success of orthopedic surgeons.…”
Section: Introductionmentioning
confidence: 99%